2019
DOI: 10.1158/1538-7445.sabcs18-p5-04-28
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P5-04-28: A potential role for IL6ST mediating endocrine resistance in breast cancer via interaction with the ER signaling pathway

Abstract: Background Interest in the ubiquitously expressed transmembrane receptor IL6ST (gp130) has developed as it has been identified as a predictive biomarker of endocrine treatment response in breast cancer patients and is included in the 'Endopredict' test. At least seven cytokines (IL-6, OSM, LIF, IL-11, CNTF, IL-27, CT-1) signal via IL6ST. Interleukin-6 (IL-6) can mediate effects via two signaling pathways; classic signaling (through the membrane-bound IL-6 receptor, IL-6R) and trans-signaling (vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…There is limited information available regarding IL6ST in breast cancers (15)(16)(17)(18)(19). One recent report documented expression of full-length IL6ST in three breast cancer cell lines, MCF-7, T47D, and ZR-75-1 (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is limited information available regarding IL6ST in breast cancers (15)(16)(17)(18)(19). One recent report documented expression of full-length IL6ST in three breast cancer cell lines, MCF-7, T47D, and ZR-75-1 (15).…”
Section: Discussionmentioning
confidence: 99%
“…There is limited information available regarding IL6ST in breast cancers (15)(16)(17)(18)(19). One recent report documented expression of full-length IL6ST in three breast cancer cell lines, MCF-7, T47D, and ZR-75-1 (15). Another study reported that IL6ST expression could predict which patients with estrogen receptor positive (ER+) ductal carcinoma in situ (DCIS) might benefit from endocrine therapy as an adjunctive treatment to surgery (16).…”
Section: Discussionmentioning
confidence: 99%